A comparison of surface and subsurface controls on summer temperature in a headwater stream. Issue 4 (8th April 2013) - MacDonald, Ryan J.; Boon, Sarah; Byrne, James M.; Silins, Uldis
Abstract This study compared summer stream temperature between two years in the Star Creek catchment, Alberta, a headwater basin on the eastern slopes of the Canadian Rocky Mountains. Star Creek is a subsurface water dominated stream, which represents important habitat for native salmonid species. Hydrometeorological data from May to September of 2010 and 2011 accompanied by stream energy budget calculations were used to describe the drivers of stream temperature in this small forested stream. Mean, maximum, and minimum weekly stream temperatures were lower from May to August and higher in September 2011 compared to 2010. Weekly range in stream temperature was also different between years with a higher range in 2010. Inter‐annual stream temperature variation was attributed discharge differences between years, shown to be primarily governed by catchment‐scale moisture conditions. This study demonstrates that both meteorological and hydrological processes must be considered in order to understand stream temperature response to changing environmental conditions in mountainous regions. Copyright © 2013 John Wiley & Sons, Ltd.